2019
DOI: 10.3389/fgene.2019.01214
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Co-Expression Network Analysis Identifies Critical Genes in the Development of Heart Failure After Acute Myocardial Infarction

Abstract: Background: The development of heart failure (HF) remains a common complication following an acute myocardial infarction (AMI), and is associated with substantial adverse outcomes. However, the specific predictive biomarkers and candidate therapeutic targets for post-infarction HF have not been fully established. We sought to perform a weighted gene co-expression network analysis (WGCNA) to identify key modules, hub genes, and possible regulatory targets involved in the development of HF following AMI. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 79 publications
(116 reference statements)
0
77
0
3
Order By: Relevance
“…WGCNA has been used to screen genes for different processes in cardiovascular disease such as coronary artery disease [24], congestive HF (CHF) and valvular heart disease (VHD). The use of WGCNA for the discovery of biomarkers related to cardiac arrest after acute myocardial infarction (AMI) has also been reported in a previous study [25] which identified six key genes with a great prognostic value for the progression of HF post-AMI. However, more studies are needed to dissect and decipher the genes involved in left ventricular failure.…”
Section: Introductionmentioning
confidence: 87%
“…WGCNA has been used to screen genes for different processes in cardiovascular disease such as coronary artery disease [24], congestive HF (CHF) and valvular heart disease (VHD). The use of WGCNA for the discovery of biomarkers related to cardiac arrest after acute myocardial infarction (AMI) has also been reported in a previous study [25] which identified six key genes with a great prognostic value for the progression of HF post-AMI. However, more studies are needed to dissect and decipher the genes involved in left ventricular failure.…”
Section: Introductionmentioning
confidence: 87%
“…Mo et al [ 22 ] used the dataset of GSE59867 as the validation dataset to verify the four gene signatures ( NCF2 , MYO1F , S1PR4 , and FCN1 ) identified by WGCNA in GSE90074. A recent study by Niu et al identified 6 hub genes ( BCL3 , HCK , PPIF , S100A9 , SERPINA1 , and TBC1D9B ) by analyzing GSE59867 using WGCNA [ 23 ]. Though using the same dataset and similar analysis method, our study was different from their study.…”
Section: Discussionmentioning
confidence: 99%
“…As a step further than GWAS, weighted gene co-expression network analyses (WGCNA) allow functional interpretations of gene network modules (152). In a recent WGCNA analyses, the six hub genes BCL3, HCK, PPIF, S100A9, SERPINA1, and TBC1D9B were identified in HF patients after acute MI and could potentially serve as early prognostic biomarkers for HF (152). These hub genes might be involved in the development of HF by regulating local and systemic inflammatory pathways (152).…”
Section: Genome Wide Association Studies (Gwas) and Weighted Gene Co-mentioning
confidence: 99%